ADAMTS5-specific gapmer release from an albumin biomolecular assembly and cartilage internalization triggered by ultrasound - Marwa Elkhashab; Goncalo Barreto; Maxime Fauconnier; Yohann Le Bourlout; Laura B. Creemers; Heikki J. Nieminen; Kenneth A. Howard (Drug Delivery)
Objective Antisense oligonucleotides (ASOs) have reached the clinic; however, they lack tissue specificity. Albumin is a plasma-abundant macromolecule that has been shown to accumulate in inflamed tissues. In this work, we have designed a recombinant human albumin (rHA)-based biomolecular assembly incorporating a DNase-resistant phosphorothioate-based complementary oligonucleotide (cODN) and an anti-ADAMTS5 ASO for potential delivery to inflamed sites. Ultrasound (US) was used to trigger ASO release from the assembly and enhance internalization into articular cartilage.Methods A phosphorothioate cODN was conjugated to rHA through a maleimide cross-linker after which, a therapeutic ADAMTS5-specific gapmer ASO was annealed to the cODN. ASO release was assessed after exposing the biomolecular assembly to different US conditions using an US-actuated medical needle operating at 32.2 kHz. Gene silencing efficiency of US-treated anti-ADAMTS5 ASO was assessed in human primary chondrocytes isolated from osteoarthritic patients. US-mediated ASO penetration into articular cartilage was assessed on ex vivo bovine articular cartilage.Results ASO release was observed after exposure to US waves in continuous mode conditions that did not compromise ASO gene silencing efficiency in human chondrocytes. Furthermore, US increased ASO internalization into bovine articular cartilage after 30 min of application without detrimental effects on chondrocyte viability.Conclusion A medical needle driven by continuous US waves at 32.2 kHz has the capability of disassembling a duplex oligonucleotide and enhancing released ASOs internalization into articular cartilage. This work offers the potential delivery and the local triggered release of ASOs at the surface of articular cartilage providing potential benefits for the treatment of diverse cartilage pathologies.